Production of biodiesel from jatropha oil using phase boundary catalyst - Mohd Ikhwan, Mohd Rasid (2010)
Biodiesel is an alkyl ester from reactions of fatty acids with short chain alcohols made by the transesterification of oils or fats from either plants or animals sources in the presence of a catalyst.The objective of this project is to give elemental insight into the transesterification of triglycerides on heterogeneous phase boundary catalyst.In an effort to identify catalyst characteristics that would be ideal for biodiesel synthesis,this study present the result from BET Surface Area analysis,Hydrophobic-Hydrophilic test, Thermogravimetric analysis(TGA),X-Ray Diffraction(XRD) analysis,Scanning Electron Microscopy(SEM) analysis, Transmission Electron Microscopy(TEM)analysis and catalytic activity of heterogeneous phase boundary base catalysts with different hydrophobicity in the transesterification of jatropha oil.The potassium fluoride(KF)anchored on solid material is believed to be capable in catalyzing the transesterification of triglycerides,but this reaction is favorable with the catalyst that possesses hydrophobic environment for the triglycerides to adsorb on the base sites to produce the fatty acid methyl esters.In this research,four types of catalysts were prepared.The first design was calcined zirconium.The second catalyst is with full coverage of potassium fluoride(KF)attached on the zirconia surface creating base sites.This catalyst is believed to be less hydrophilic than the first design.The third catalyst designed was prepared by partially attachment of octadecyltrichlorosilane(OTS)and KF while the fourth catalyst was modified by partially attachment of the chlorotrimethylsilane(CTMS)and KF onto the zirconia surface. The purpose of using OTS and CTMS are to create hydrophobic environment around the catalyst and to determine the enhancement of hydrophobic groups to the reaction.The catalytic results suggest that the third design catalysts perform very well with catalyst dosage of 5 wt% at 65 ºC, ratio of methanol and jatropha oil at 9:1 with 8 hours reaction time,yield 85 % conversion of methyl ester.